PREVALENSI PERSALINAN DENGAN TINDAKAN SEKSIO SESAREA DI RSUD DR MOEWARDI SURAKARTA PERIODE 2007 - Tulis, Iva Irama (2008)
The aim of this research is to know the delivery cases ended by sectio cesarean operation in RSUD Dr. Moewardi of Surakarta. Sectio cesarean is delivery, where infant born through incision of uterus, the frequency is increase. The most generally indications is cefalopelvic disproportion. The operation technique is sectio cesarean peritoneal and extraperitoneal. Complication of sectio cesarean can be occurred of mother and child. We attentive once a cesarean not always a cesarean. The research using descriptive survey research with retrospective method. Data is taken from Sub Section of Medical Documentation of RSUD Dr. Moewardi of Surakarta. The result shows that frequency of sectio cesarean in RSUD Dr. Moewardi of Surakarta as 28,14%, with most indication as preeclampsia, eclampsia is as 15,02. The age between 20-30 years old is 52,24%. While the most parity of nullipara as 47,75%. The implementation operation is SCTP. And the condition of baby's sectio cesarean action is alive as 95,55%. We should give many attentions and increase the antenatal care (ANC) treatment through illumination and medical training as well as increase service of reconciliation procedures and delivering patient so that the pregnant women feel comfortable